Hakikat Pendidikan Kewarganegaraan sebagai Landasan Pembentukan Karakter Pelajar Pancasila - Defliyanti Saragih, Mima; Novi Yanti Lumbantobing, Joy; leryaldo Sinaga, Manotar; Fhutu Neva, Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the need to strengthen the character of Pancasilastudents amid global challenges and the rapid pace of digitalization that affects themoral values of the younger generation. Civic Education (PKn) has a strategic rolein instilling national, moral, and humanitarian values rooted in Pancasila as thefoundation of the state. The purpose of this study is to analyze the essence of CivicEducation as the foundation for shaping the character of Pancasila students whoare faithful, noble, independent, critical thinkers, cooperative, and globally diverse.The method used is library research by examining various scientific sources suchas books, journals, and national education policy documents. The results of thestudy show that the internalization of Pancasila values in Civic Education learningrequires the integration of cognitive, affective, and psychomotor dimensionssupported by the roles of teachers, the school environment, and the family. Inaddition, project-based and contextual learning models have proven to be effectivein transforming values into the actual behavior of students. In conclusion, CivicEducation plays a major role as the foundation in shaping Pancasila students whonot only understand national values theoretically, but are also able to implementthem in their daily lives as a manifestation of the civilized and integrity-basedcharacter of the Indonesian nation